Attitude for Physics: The Condition of High School Students - Tanti, T; Astalini, A; Kurniawan, D A; Darmaji, D; Puspitasari, T O; Wardhana, I (Department of Physics, Faculty of Mathematics and Natural Sciences, 2021)
The purpose of this study was to determine student attitudes towards learning physics in high schools in the city of Jambi and Batang Hari. The method used is a survey type quantitative research method. The data collection technique in this study used purposive sampling technique with the research instrument used was a questionnaire instrument. The data analysis used in this research is descriptive analysis. Based on the results of the study, attitudes based on indicators of social implications, scientist normality, and attitudes towards physics research conducted at SMAN 8 Jambi City with the physics attitudes at SMAN 10 Batang Hari can be concluded that the results displayed are different from the category results and the number of respondents. So that there are different conditions from the two SMAs. This comparison also shows that SMAN 8 Kota Jambi shows a better attitude seen from the percentage and number of respondents.